Clinical, epidemiological, and therapeutic profile of dermatophytosis - Carla Andréa Avelar Pires; Natasha Ferreira Santos da Cruz; Amanda Monteiro Lobato; Priscila Oliveira de Sousa; Francisca Regina Oliveira Carneiro; Alena Margareth Darwich Mendes (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: The cutaneous mycoses, mainly caused by dermatophyte fungi, are among the most common fungal infections worldwide. It is estimated that 10% to 15% of the population will be infected by a dermatophyte at some point in their lives, thus making this a group of diseases with great public health importance. OBJECTIVE: To analyze the clinical, epidemiological, and therapeutic profile of dermatophytosis in patients enrolled at the Dermatology service of Universidade do Estado do Pará, Brazil, from July 2010 to September 2012. METHOD: A total of 145 medical records of patients diagnosed with dermatophytosis were surveyed. Data were collected and subsequently recorded according to a protocol developed by the researchers. This protocol consisted of information regarding epidemiological and clinical aspects of the disease and the therapy employed. RESULTS: The main clinical form of dermatophyte infection was onychomycosis, followed by tinea corporis, tinea pedis, and tinea capitis. Furthermore, the female population and the age group of 51 to 60 years were the most affected. Regarding therapy, there was a preference for treatments that combine topical and systemic drugs, and the most widely used drugs were fluconazole (systemic) and ciclopirox olamine (topical). CONCLUSION: This study showed the importance of recurrent analysis of the epidemiological profile of dermatophytosis to enable correct therapeutic and preventive management of these conditions, which have significant clinical consequences, with chronic, difficult-totreat lesions that can decrease patient quality of life and cause disfigurement.